A comparative study of the effect of the dose and exposure duration of anabolic androgenic steroids on behavior, cholinergic regulation, and oxidative stress in rats - Bueno, Andressa; Carvalho, Fabiano B.; Gutierres, Jessié M.; Lhamas, Cibele; Andrade, Cinthia M. (PLOS ONE, 2017)
The aim of this study was to assess if the dose and exposure duration of the anabolic androgenic steroids (AAS) boldenone (BOL) and stanazolol (ST) affected memory, anxiety, and social interaction, as well as acetylcholinesterase (AChE) activity and oxidative stress in the cerebral cortex (CC) and hippocampus (HC). Male Wistar rats (90 animals) were randomly assigned to three treatment protocols: (I) 5 mg/kg BOL or ST, once a week for 4 weeks; (II) 2.5 mg/kg BOL or ST, once a week for 8 weeks; and (III) 1.25 mg/kg BOL or ST, once a week for 12 weeks. Each treatment protocol included a control group that received an olive oil injection (vehicle control) and AAS were administered intramuscularly (a total volume of 0.2 ml) once a week in all three treatment protocols. In the BOL and ST groups, a higher anxiety level was observed only for Protocol I. BOL and ST significantly affected social interaction in all protocols. Memory deficits and increased AChE activity in the CC and HC were found in the BOL groups treated according to Protocol III only. In addition, BOL and ST significantly increased oxidative stress in both the CC and HC in the groups treated according to Protocol I and III. In conclusion, our findings show that the impact of BOL and ST on memory, anxiety, and social interaction depends on the dose and exposure duration of these AAS.